(untitled) - Lauer, Roberts H. (Boston, 2000)
Offering the most positive and practical approach to the study of marriage and family life with a manageable amount of sociological theory and research citations, this text is centered around the theme of enhancing intimacy within marriage and the family. While providing a comprehensive overview of the progression from dating to marriage and family, the authors systematically draw out principles that students can use to protect and nurture their own intimate relationships, making this not only a text, but a practical guide for students as well.
Keywords: Marriage,Family; United states,United states